Industrial relations, flexibility, and the EU social dimension - Faber, P; Faber, P. A. (1999)
This study sets out to explore employer response to the EU social dimension, in answer to the question, "How are employers in the UK and Germany responding to the EU social dimension, and why?" Using case study evidence from nine large British and German engineering companies, as well as material from employers' associations at all levels, it is argued that there is little employer support for extending the social dimension. Focusing on micro-economic aspects of the debate, it is also argued that a common feature in both British and German employer opposition is a concern for the impact of EU industrial relations regulation on firm-level flexibility. This stands in direct contradiction of the EU Commission's own contentions about the flexibility-enhancing effects of its social policy measures, and appears paradoxical in light of earlier research findings of a German flexibility advantage over UK rivals on account of the country's well-structured regulatory framework for industrial relations. Evidence from participant companies, however, suggests that, in the global environment of the late 1990s, much of Germany's former flexibility advantage has been eroded, and the regulation-induced limitations on both the pace and scale of change are increasingly onerous to German companies. German managers perceive a need for targeted deregulatory reform of their industrial relations system; by strengthening (and often extending) existing industrial relations regulation, EU social policy measures meet with firm disapproval. In the UK, by contrast, the changed context has contributed to a significant increase in firm-level flexibility. British companies now operate to levels of flexibility often in advance of their German counterparts, at far lower 'cost' in terms of the time taken, and the extent to which change measures are compromised, to reach agreement. For British managers, EU social policy measures are perceived as a threat to these beneficial arrangements, and vigorously opposed. The thesis concludes by suggesting that such fixed opposition, in the face of Commission determination to extend the EU social dimension, points to an escalation of the controversy surrounding the social dimension.